ACCOUNTING FOR EMBEDDED DERIVATIVES - Yuliya A. Tarasova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzed the existing order of discounting in-built finance tools derivatives in accordance with international and Russian standards and found insufficient methodological development and questionability of many issues connected with identification and further discount of in-built finance tools derivatives. Such terms as ‘hybrid contract’ and ‘in-built finance tools derivative’ were defined. An acute classification of the most widely-spread types of in-built finance tools derivatives was put forward. The author advanced her own algorithm of identifying in-built finance tools derivatives in contracts in order to develop theoretical and methodological foundations in the field of such tools discount.